2017
DOI: 10.1002/jcp.26276
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potency of mTOR signaling pharmacological inhibitors in the treatment of proinflammatory diseases, current status, and perspectives

Abstract: Mammalian target of rapamycin (mTOR) signaling pathway controls cell energy metabolism. There is an interplay between mTOR and proinflammatory signaling pathways, supporting the role of the pathway in the pathogenesis of inflammatory diseases. Inhibition of mTOR signaling using specific pharmacological inhibitors could offer therapeutic promise in several inflammatory-associated diseases. In this review, we summarize recent findings on the regulatory effects of mTOR signaling on inflammation and the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…Activated AKT can cause a series of phosphorylation cascade reactions and regulate vital downstream effector molecules, like mTOR to exert its biological effect (Dirk et al, 2018;Li et al, 2019). PI3K/AKT/mTOR signaling pathway controls cell growth, proliferation, cell polarity and cytoskeleton, and EMT and angiogenesis (Peng et al, 2014;Arash and Amirhossein, 2017;Falguni et al, 2018). Recent studies have shown that activated PI3K/AKT/mTOR signaling pathway can induce EMT process, especially E-cadherin level and inhibit matrix metalloproteinases (MMPs) (Karimi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Activated AKT can cause a series of phosphorylation cascade reactions and regulate vital downstream effector molecules, like mTOR to exert its biological effect (Dirk et al, 2018;Li et al, 2019). PI3K/AKT/mTOR signaling pathway controls cell growth, proliferation, cell polarity and cytoskeleton, and EMT and angiogenesis (Peng et al, 2014;Arash and Amirhossein, 2017;Falguni et al, 2018). Recent studies have shown that activated PI3K/AKT/mTOR signaling pathway can induce EMT process, especially E-cadherin level and inhibit matrix metalloproteinases (MMPs) (Karimi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mTOR, a serine/threonine protein kinase, forms two complexes with distinct proteins: mTORC1 and mTORC2. These proteins are direct targets of RAPA and regulate protein synthesis; cellular proliferation, differentiation and survival; and lipid metabolism (Soltani et al, 2018). The mTORC1 composite consists mainly of mTOR, raptor, and G-protein β-subunit protein (GßL).…”
Section: Rapamycinmentioning
confidence: 99%
“…Rapamycin (sirolimus) is an inhibitor of mammalian target of rapamycin (mTOR). It not only blocks host pathways needed for viral replication [ 11 13 ], but also modulates the immune responses during infection [ 14 16 ]. Consequently, it may be a promising drug for treating influenza.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that mTORC2 may contribute to the regulation of apoptosis by the viral NS1 protein during infection [ 11 , 21 ]. Aberrant mTOR activation plays critical roles in the pathogenesis of proinflammatory diseases including lipopolysaccharide induced-ALI, sepsis, atherosclerosis and neurodegenerative diseases, which make mTOR an important therapeutic target for these diseases [ 14 ]. Whether mTOR activation by influenza virus contributes to pathogenesis has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%